Analisis Efektivitas Biaya Penggunaan Antibiotik Pada Anak Penderita Demam Tifoid Di Rsud Sukoharjo 2016 - Permana Sari, Ajeng; , Rima Munawaroh, M.Sc., Apt; , Mariska Sri Harlianti, M.Sc., Apt (2017)
Typhoid fever remains as 10 popular diseases in Indonesia, 91% where the cases encountered in the children 5-12 years old. This disease is caused by an infection of the digestive tract by the bacteria called Salmonella typhi. Antibiotics are the primary choice of drug for the treatment of typhoid fever. In this case, it is necessary to do a cost-effectiveness analysis in order to help in making a decision to choose for the effective antibiotics based on benefits and costs. This research has purpose to compare the cost and effectiveness of antibiotics usage in children with typhoid fever in the inpatient installation of Public Regional Hospital Sukoharjo in 2016 by using ACER and ICER method. Research was conducted through a non-experimental in RSUD Sukoharjo. The data of children patient with typhoid fever obtained from the installation of medical records and the administration section. The data taken for the analysis of cost effectiveness is the data of antibiotic therapy effectiveness and the direct medical costs. The results in RSUD Sukoharjo of antibiotic studies used by patients with typhoid fever were chloramphenicol (7.5%), ceftriaxone (22.5%) and cefotaxime (70%). The results of this study concluded that treatment of typhoid fever the most cost-effective in anggrek and mawar space based on the value of the ACER and ICER is an antibiotic ceftriaxone with an average length of stay respectively 2.25 days and 2.8 days.